2019
DOI: 10.1038/s41387-019-0086-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the resistant starch on glucose, insulin, insulin resistance, and lipid parameters in overweight or obese adults: a systematic review and meta-analysis

Abstract: Background The role of resistant starch (RS) in glucose, insulin, insulin resistance or sensitivity, and lipid parameters have been reported in several studies and remained controversial. A pooled analysis which assessed these parameters has not been performed. Thus, we conducted a meta-analysis to sum up existing evidence about the issue. Methods We searched in MEDLINE and PUBMED for studies that were published before November 2018. Meta-analysis of diabetics and nondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 33 publications
5
52
0
1
Order By: Relevance
“…Some studies have evaluated the effect of cellulose, an insoluble dietary fiber, on blood glucose levels in humans [ 36 ], reporting a decrease in postprandial glucose levels by its intake [ 37 , 38 ]. In other previous studies, the effect of consumption of resistant starch in blood glucose and insulin sensitivity has been reported, which indicated that resistant starch intake improves fasting blood glucose levels and insulin sensitivity [ 39 , 40 ]. Insoluble dietary fiber is involved in postprandial blood glucose changes by the acceleration of the secretion of glucose-dependent insulinotropic polypeptide (GIP) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated the effect of cellulose, an insoluble dietary fiber, on blood glucose levels in humans [ 36 ], reporting a decrease in postprandial glucose levels by its intake [ 37 , 38 ]. In other previous studies, the effect of consumption of resistant starch in blood glucose and insulin sensitivity has been reported, which indicated that resistant starch intake improves fasting blood glucose levels and insulin sensitivity [ 39 , 40 ]. Insoluble dietary fiber is involved in postprandial blood glucose changes by the acceleration of the secretion of glucose-dependent insulinotropic polypeptide (GIP) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The digestion rate of resistant starch has physiological implications such as in reducing post-prandial glycemic response in healthy [ 7 ], overweight or obese adults [ 8 ] and in populations at risk for type-2 diabetics [ 9 ]. Thus, replacement of digestible starch with resistant starch have beneficial glycemic effects in healthy and pre-diabetics [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compliance with the supplements was monitored every week by a telephone call. None of the subjects completing the study had any serious adverse events such as gastrointestinal, central nervous system, skin symptoms, and hypoglycemia [1718].…”
Section: Methodsmentioning
confidence: 99%